140k views
21 votes
What is the solution to the following equation? -6(x-2) + 3x = -3(x + 3) + 21

(This is not multiple choice and I need the answer in number form, with explanation please) :)

2 Answers

5 votes
-6(x+2) + 3x = -3(x+3) + 21

-6x - 12 + 3x = -3x - 9 + 21

-3x - 12 = -3x + 12

-3x + 3x = 12 + 12

0 = 24

Sorry but this equation has no solution.
-3x + 3x = 0, x is cancelled out so we can’t find ‘x’.
User Nerdherd
by
4.9k points
11 votes

9514 1404 393

Answer:

no solution

Explanation:

Simplifying the given equation, you have ...

-6(x -2) +3x = -3(x +3) +21 . . . . . given

-6x +12 +3x = -3x -9 +21 . . . . . . eliminate parentheses

-3x +12 = -3x +13 . . . . . . . . . . . . collect terms

0 = 1 . . . . . . . . . . . . . add (3x-12) to both sides

There is no value of x that will make this true.

The equation has NO SOLUTION.

User Chris Hep
by
5.1k points